HUMAN SECURITY AND THE ROLE OF NATIONAL HUMAN RIGHTS INSTITUTIONS IN THE ENFORCEMENT OF LANGUAGE RIGHTS POLICY IN SRI LANKA - Bawa, Mohamed Mowjoon Atham (Indonesian Journal of International Law, 2013)
Human security is about protecting people, however it has gone ahead of the traditional security definitions and focusing on evolutionary changes in the human security infrastructure. The arguments over human security are not new. Human security is a comparable undisciplined argument for a return to enlightenment liberalism. United Nations Commission on Human Security defines human security as the protection of “the vital core of all human lives in ways that enhance human freedoms and fulfilment.” As such, this encompassing approach does not distinguish “freedom from fear” and “freedom from want” for individual citizens. This paper will explain 2 key points which are language rights as human rights in the Sri Lankan context and National Institutions. It is based on during the civil war the Sri Lankan citizens were not able to enjoy the language access efficiently therefore the innocent people were not able to express themselves in their own language and were treated as terrorists rather than the normal citizens of Sri Lanka.